Sex-specific effects of fecal microbiota transplantation on TBI-exacerbated Alzheimer’s disease pathology in mice - Soriano, Sirena; Marshall, Austin; Holcomb, Morgan; Flinn, Hannah; Burke, Marissa; Kara, Göknur; Scalzo, Paula; Villapol, Sonia (Frontiers in Microbiology, 2026)
BackgroundTraumatic brain injury (TBI) accelerates Alzheimer’s disease (AD) pathology and neuroinflammation, potentially via gut-brain axis disruptions. Whether restoring gut microbial homeostasis mitigates TBI-exacerbated AD features remains unclear, particularly with respect to sex differences.ObjectiveThe goal of our study was to test whether fecal microbiota transplantation (FMT) modifies amyloid pathology, neuroinflammation, gut microbial composition, metabolites, and motor outcomes in male and female 5xFAD mice subjected to TBI.MethodsMale and female 5xFAD mice received sham treatments or controlled cortical impact, followed 24 h later by vehicle (VH) or sex-matched FMT from C57BL/6 donors. Assessments at baseline, 1-, and 3-days post-injury (dpi) included Thioflavin-S and 6E10 immunostaining for Aβ, Iba-1 and GFAP for glial activation, lesion volume, rotarod performance, 16S rRNA sequencing for microbiome profiling, serum short-chain fatty acids (SCFAs), and gut histology.ResultsTBI increased cortical and dentate gyrus Aβ burden, with females showing greater vulnerability. FMT reduced Aβ deposition in sham animals and shifted plaque morphology but did not attenuate TBI-induced amyloid escalation. FMT differentially modulated glial responses by sex and region (reduced microgliosis in males) without altering lesion volume at 3 dpi. Rotarod performance was better in sham females compared to males and declined in FMT-treated TBI females. Fecal microbiome alpha diversity and richness were unchanged, while beta diversity revealed marked, time-dependent community shifts after TBI that were slightly altered by FMT. Gut morphology remained broadly intact, but crypt width increased after TBI, particularly in males.ConclusionIn 5xFAD mice, TBI drives sex-dependent worsening of amyloid pathology, neuroinflammation, and dysbiosis. Acute FMT partially restores microbial composition and plaque features in sham animals but fails to reverse TBI-induced neuroinflammation or motor deficits. These findings underscore the context- and sex-dependence of microbiome interventions and support longer-term, sex-specific strategies for AD with comorbid TBI.